Lactose hydrolysis by free and fibre-entrapped ß-galactosidase from Streptococcus thermophilus - Yang, Zhennai; Pahkala, Eero; Tupasela Tuomo (Agricultural Research Centre of Finland, The Scientific Agricultural Society of Finland, The Finnish Society of Dairy Science, 1993)
Streptococcus thermophilus 11F kannalla tuotettiin b-galaktosidaasia, joka osittain puhdistettiin asetoni- ja ammoniumsulfaattifraktioinnilla sekä ioninvaihtokromatografialla Q Sepharose FF-pylväässä. Entsyymin aiheuttamaan laktoosin pilkkoutumiseen vaikuttivat laktoosin pitoisuus, eri sokerit ja maidon valkuaisaineet. Korkein hydrolyysiaste puskuriliuoksessa saavutettiin 15 % laktoosipitoisuudessa. Lisättäessä maitoon 2 % joko laktoosia, glukoosia, galaktoosia tai sakkaroosia laktoosin hydrolyysi heikkeni. Seerumin albumiini sekä as ja b-kaseiinien yhdistelmä aktivoi entsyymiä. Maidon kaseiinien pääkomponentin, (as-kaseiinin vaikutus hydrolyysiin oli vähäisempi kuin b- tai k-kaseiinin. Kuituun sidotun entsyymin lämpötilaoptimi oli 57°C ja pH optimi välillä 7,5-9,0 käytettäessä O-nitrofenyyli-b-D-galactopyranosiidia subtraattina. Kierrätettäessä kuorittua maitoa tai heraa kuituun sidotulla entsyymillä täytetyssä lasikolonnissa saavutettiin 55°C lämpötilassa 7 tunnissa 47,9 % ja 11 tunnissa 49,5 % laktoosin hydrolyysiaste.

To study lactose hydrolysis by b-galactosidase, this enzyme was produced from Streptococcus thermopihilus strain 11F and partially purified by acetone and ammonium sulphate fractionation, and ion exchange chromatography on a Q Sepharose FF column. Lactose hydrolysis by the enzyme was affected by lactose concentrations, sugars and milk proteins. The maximum extent of lactose hydrolysis in buffer was obtained with a 15% lactose concentration. Addition of 2% of lactose, glucose, galactose or sucrose in milk inhibited the enzymatic hydrolysis. The enzyme was activated by bovine serum albumin and a combination of as-casein and b-casein. Of the casein fractions, the principal fraction, as-casein, was less effective than b-casein and k-casein. The fibre-entrapped enzyme had a temperature optimum of 57°C, and a pH optimum from 7.5 to at least 9.0 with O-nitrophenyl-b-D-galactopyranoside as substrate. By recycling with whey and skim milk through a jacketed glass column (1.6 cm x 30 cm) loaded with fibre-entrapped enzyme at 55°C, a lactose hydrolysis of 49.5% and 47.9% was achieved in 11 h and 7 h respectively.
Keywords: hydrolyysi; lactose hydrolysis; Streptococcus thermophilus; b-galactosidase; fibre-entrapped enzyme